Development of a geometrically accurate and adaptable finite element head model for impact simulation: the Naval Research Laboratory–Simpleware Head Model. Issue 1 (2nd January 2016) - Cotton, R.T.; Pearce, C.W.; Young, P.G.; Kota, N.; Leung, A.C.; Bagchi, A.; Qidwai, S.M.
Abstract : This study demonstrates a novel model generation methodology that addresses several limitations of conventional finite element head models (FEHM). By operating chiefly in image space, new structures can be incorporated or merged, and the mesh either decimated or refined both locally and globally. This methodology is employed in the development of a highly bio-fidelic FEHM from high-resolution scan data. The model is adaptable and presented here in a form optimised for impact and blast simulations. The accuracy and feasibility of the model are successfully demonstrated against a widely used experimental benchmark in impact loading and through the investigation of potential brain injury under blast overpressure loading.